How do you solve using gaussian elimination or gauss-jordan elimination, x_1 +2x_2 − x_3 +3x_4 =2x1+2x2x3+3x4=2, 2x_1 + x_2 + x_3 +3x_4 =12x1+x2+x3+3x4=1, 3x_1 +5x_2 − 2x_3 +7x_4 =33x1+5x22x3+7x4=3, 2x_1 +6x_2 − 4x_3 +9x_4 =82x1+6x24x3+9x4=8?

1 Answer
Aug 7, 2017

The solutions are x_4=2 x4=2, x_3x3 free, x_1=-2-x_3, x_2=-1+x_3x1=2x3,x2=1+x3

Explanation:

We perform the Gauss Jordan elimination with the augmented matrix

((1,2,-1,3,:,2),(2,1,1,3,:,1),(3,5,-2,7,:,3),(2,6,-4,9,:,8))

R4larrR4-2R1, => , ((1,2,-1,3,:,2),(2,1,1,3,:,1),(3,5,-2,7,:,3),(0,2,-2,3,:,4))

R3larrR3-3R1, => , ((1,2,-1,3,:,2),(2,1,1,3,:,1),(0,-1,1,-2,:,-3),(0,2,-2,3,:,4))

R2larrR2-2R1, => , ((1,2,-1,3,:,2),(0,-3,3,-3,:,-3),(0,-1,1,-2,:,-3),(0,2,-2,3,:,4))

R2larrR1-R4, => , ((1,0,1,0,:,-2),(0,-3,3,-3,:,-3),(0,-1,1,-2,:,-3),(0,2,-2,3,:,4))

R4larrR4+2R3, => , ((1,0,1,0,:,-2),(0,-3,3,-3,:,-3),(0,-1,1,-2,:,-3),(0,0,0,-1,:,-2))

R4larr(R4)/(-1), => , ((1,0,1,0,:,-2),(0,-3,3,-3,:,-3),(0,-1,1,-2,:,-3),(0,0,0,1,:,2))

R2larr(R2)/(-3), => , ((1,0,1,0,:,-2),(0,1,-1,1,:,1),(0,-1,1,-2,:,-3),(0,0,0,1,:,2))

R3larrR3+R2, => , ((1,0,1,0,:,-2),(0,1,-1,1,:,1),(0,0,0,-1,:,-2),(0,0,0,1,:,2))

R3larr(R3)/(-1), => , ((1,0,1,0,:,-2),(0,1,-1,1,:,1),(0,0,0,1,:,2),(0,0,0,1,:,2))

R4larrR4-R3, => , ((1,0,1,0,:,-2),(0,1,-1,1,:,1),(0,0,0,1,:,2),(0,0,0,0,:,0))

R2larrR2-R3, => , ((1,0,1,0,:,-2),(0,1,-1,0,:,-1),(0,0,0,1,:,2),(0,0,0,0,:,0))

The solutions are x_4=2 , x_3 free, x_1=-2-x_3, x_2=-1+x_3